2017
DOI: 10.24908/pceea.v0i0.6471
|View full text |Cite
|
Sign up to set email alerts
|

Imagery and Gender in Canadian Engineering Recruitment Documents

Abstract: -Gender imbalance is a persistent issueacross Canadian engineering programs. Efforts have been made to increase the enrolment of undergraduate women in engineering, but reaching gender parity in engineering has been an elusive goal. This research examines program recruitment images and videos from 18 Canadian engineering university websites. Using content analysis and thematic coding of video transcriptions, we coded 440 unique images and 37 recruitment videos. We find that women students are overrepresented i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…A total of 854 individuals appeared in images, and they were coded as students [5], faculty, industry members, and people whose role was unknown. Of these, 170 were faculty (21.8% of whom were women), and 104 were industry members (35.6% of whom were women) ( Table 1).…”
Section: Image Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 854 individuals appeared in images, and they were coded as students [5], faculty, industry members, and people whose role was unknown. Of these, 170 were faculty (21.8% of whom were women), and 104 were industry members (35.6% of whom were women) ( Table 1).…”
Section: Image Resultsmentioning
confidence: 99%
“…Based on our previous work, we suspect that a lot of importance is placed on the inclusion of women in recruitment materials, as we found that female students were being represented well above their actual enrolled levels [5]. This representation is notable given that both male and female students more often draw men when asked to draw a scientist [6], and given that textbooks for prerequisite high school science courses are likely to show only a small number of women scientists [7], along with other forms of subtle sexism in images [8].…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations